Ecological Risk Associated with Heavy Metals in the Hydrographic Basin of the Cerna River, Hunedoara County - Irina Monica SIMO; Mihaela-Cătălina HERGHELEGIU; Vlad Alexandru PĂNESCU; Mihail Simion BELDEAN-GALEA (Aerul şi Apa: Componente ale Mediului)
Pollution with heavy metals has raised substantial concerns worldwide due to their toxicity and persistence in environmental factors. The current research aims to provide a detailed understanding of the level of contamination in the Cerna River basin with the following heavy metals: copper (Cu), cadmium (Cd), chromium (Cr), lead (Pb), nickel (Ni), arsenic (As) and zinc (Zn). The collection of surface water was performed in two sampling campaings, the first one in October 2023, and second one in August 2024, resulting in ten sampling points from the Cerna River and its main tributaries, from Hunedoara County. The selected sampling points are the following: P1 - Cerna River at the confluence with Mureș River, P2 - Cerna River in Sântuhalm, P3 - Teliuc River in Teliucul Inferior, P4 - Toplița River in Toplița, P5 - Cristur River in Cristur, P6 - Peștiș River in Peștișul Mare, P7 - Petac River in Peștișul Mic, P8 - Zlaști River in Zlaști, P9- Govâjdia River in Govâjdie, P10 - Vălarița River in Vălari village. The analysis of heavy metal content from the surface water samples was performed by atomic absorption spectrophotometry in a graphite furnace. The results on the two sampling campaign recorded the following concentrations (in μg/L): first sampling campaign carried out in October 2023, recorded the following concentrations: between 0.55-16.20 μg/L for Cr; between 1.05-2.68 μg/L for As; between 0.04-2.44 μg/L for Zn; between 0.74-24.90 μg/L for Cu; between 0.03-2.44 μg/L for Cd; between 0.12-5.30 μg/L for Pb and between 0.51-5.04 μg/L for Ni, respectively. Second campaign carried out in August 2024 recorded values between 0.50-9.54 μg/L for Cr; between 0.03-1.49 μg/L for As; between 0.03-1.00 μg/L for Zn, between 0.02-3.57 μg/L for Ni; between 0.02-1.93 μg/L for Cd; between 0.82-25.50 for Cu and between 0.14-8.71 μg/L for Pb, respectively. Considering the maximum allowed concentrations imposed by the current legislation, the heavy metals analysed in this study, namely Zn, Cr, and As, fall within the imposed values, while Cu, Cd, Pb, and Ni exceed the maximum allowed concentration in both sampling campaigns.